2019
DOI: 10.1080/17483107.2019.1629113
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an iterative rehabilitation intervention for stroke delivered remotely using mobile health technology

Abstract: Background: Telehealth affords rehabilitation professionals opportunities to expand access to intervention for people in rural areas. Complex interventions have not been adapted for remote delivery using mobile health technologies. Strategy training is a complex intervention that teaches clients skills for identifying barriers and solutions to engagement in meaningful activities. Our goal was to adapt the delivery of strategy training for remote delivery using mobile health technology. Methods:We conducted a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…These dimensions are similar to those reported by Tsai et al [60], who also identified underlying dimensions related to acceptance of e-health technology that complemented CSQ-8. It should be emphasized that these observations do not underestimate CSQ-8, a validated tool that has been applied in web-based interventions (coaching, videoconferencing, and telerehabilitation) for several conditions (e.g., diabetes, chronic obstructive pulmonary disease, stroke, depression, and spinal surgery) and to evaluate preoperative patient satisfaction [60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 86%
“…These dimensions are similar to those reported by Tsai et al [60], who also identified underlying dimensions related to acceptance of e-health technology that complemented CSQ-8. It should be emphasized that these observations do not underestimate CSQ-8, a validated tool that has been applied in web-based interventions (coaching, videoconferencing, and telerehabilitation) for several conditions (e.g., diabetes, chronic obstructive pulmonary disease, stroke, depression, and spinal surgery) and to evaluate preoperative patient satisfaction [60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 86%
“…Thus, the novel system has potential for treatment of patients with aphasia as a supplement to face-to-face therapy. Kringle et al 26 N=5 Sequential descriptive case series United States iAdapts Cognitive skills To describe lessons learned through adaptation of a complex intervention—strategy training—for delivery via mHealth technology. Strategy training can be adapted for delivery using mHealth technology, with careful consideration to methods for training participants on new technology and the intervention delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies (36.7%) were categorized as pilot, feasibility, or proof-of-concept trials. 9 , 10 , 12 , 13 , 14 , 17 , 24 , 30 , 33 , 36 , 37 , 38 , 42 , 45 , 47 , 52 , 56 , 57 In general, the studies had relatively small sample sizes, where 23 studies (46.9%) had ≀20 participants, 9 , 10 , 11 , 12 , 15 , 16 , 22 , 25 , 26 , 27 , 28 , 32 , 34 , 35 , 36 , 38 , 41 , 43 , 44 , 45 , 47 , 50 , 57 22 studies (44.9%) had between 21 and 100 participants, 13 , 14 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 29 , 30 , 31 , 33 , 40 , 42 , 46 , 49 , 51 , 52 , 53 , 54 and 4 studies (8.2%) had >100 participants (see table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar devices also exist that continuously acquire data without interference so that the patient's motor function can be evaluated in daily life [ 37 ]. The ability for patients to perform exercise assessments without a therapist makes assessments more convenient for patients and reduces the cost of medical treatment [ 38 ]. The advantages, disadvantages, and technical requirements of mHealth are summarized in Table 3 .…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 99%